One health: a comprehensive approach to improve prevention and control strategies in Leptospirosis - Hernandez-Rodriguez, Patricia; Trujillo-Rojas, Brayam (Revista de Ciências Agroveterinárias, 2022)
Leptospirosis is a zoonosis caused by Leptospira spp., a spirochete that presents serovars diversity, whose prevalence, mode of transmission and circulation depend on the ecology and complex interrelation between humans, animals, and the environment in which they coexist. In animals, it affects reproduction causing economic losses and in terms of the environment, the evidence is limited. However, the survival of the bacteria is water favors; is for this, cases of leptospirosis increase with floods and rainfall. Despite its global distribution, epidemic potential, high human mortality rate, and socioeconomic burden, this zoonosis is neglected. Furthermore, worldwide zoonoses prioritization exercises based on the impact on agriculture, human and animal health have led to leptospirosis ranking among the most important zoonoses associated with poverty. This situation reflects the need for an integral management from the regulatory institutions of human, animal, and environmental health; but one main barrier of intersectionality is how the administration is designed for these events control. The current structures lead us to reflect and tend towards a holistic approach, seeking new forms of organization, new strategies to study, control and treat leptospirosis, the control of which is the responsibility of different sectors and disciplines. The comprehensive management of leptospirosis implies a higher level of understanding of the agent and of the biological, socioeconomic, and cultural risk factors in the regions and from a practical perspective, it is necessary to promote joint work initiatives; as well as present evidence of the need for work from a "one health" perspective for a zoonosis that has become an emerging problem in public health.